Chlorine addition prior to granular activated carbon contactors improves trihalomethane control. Issue 1 (10th January 2019) - Fischer, Natalia; Ghosh, Amlan; Talabi, Binga; Seidel, Chad; Westerhoff, Paul
Abstract : Optimizing granular activated carbon (GAC) operation can reduce costs for removing disinfection byproducts or their precursors. This article investigates prechlorination to enhance the removal of total trihalomethane (TTHM) precursors and reduce TTHM concentrations in finished water. Rapid small‐scale column tests (RSSCTs) and pilot tests using virgin and reactivated GAC were conducted on water with and without prechlorination. Prechlorination (1 or 2 mg Cl2 /L) increased (by 15 and 30%, respectively) the number of bed volumes treated by GAC. On the basis of size exclusion chromatography, prechlorination followed by GAC preferentially removed low‐molecular‐weight dissolved organic carbon by GAC. Simulated distribution system (SDS) chlorination tests on GAC effluent showed lower TTHM concentrations with prechlorination. Prechlorination lowered the bromine incorporation factor values in GAC effluents after SDS tests, which suggests a reduction in toxicity potential from trihalomethanes. RSSCT results were validated by pilot testing, showing that RSSCTs can be used to optimize the prechlorination process.